IMPLEMENTASI PERAN MANAJERIAL KEPALA SEKOLAH DALAM MEREALISASIKAN MUTU PENDIDIKAN BERBASIS KURIKULUM MERDEKA DI SDN 3 KOTA SERANG - Reksa Adya Pribadi; Firdaus; Shilvi Rizky Maulida; Rizki Wulan Ningsih (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This research aims to find out and describe the implementation of the principal's managerial role in realizing the quality of independent curriculum-based education at SDN 3 Serang City. This research uses a qualitative approach with descriptive methods. Data collection was carried out through observation, interviews and documentation. This research began from November to December 2023. The research results obtained explain that the school principal has carried out various efforts and has played a role in improving the quality management of education at SDN 3 Serang City. The efforts made include various important roles in terms of leadership and school management for teachers, staff, students, infrastructure and other school supporters. The conclusion in this research is that the managerial role of the school principal is very important in realizing the quality of independent curriculum-based education. The managerial role of the school principal has been carried out in the role of EMASLEC, namely educator, manager, administrator, supervisor, leader, entrepreneur and climate creator.